2017
DOI: 10.1109/msp.2017.2738017
|View full text |Cite
|
Sign up to set email alerts
|

Performance Bounds for Parameter Estimation under Misspecified Models: Fundamental Findings and Applications

Abstract: Inferring information from a set of acquired data is the main objective of any signal processing (SP) method. In particular, the common problem of estimating the value of a vector of parameters from a set of noisy measurements is at the core of a plethora of scientific and technological advances in the last decades; for example, wireless communications, radar and sonar, biomedicine, image processing, and seismology, just to name a few.Developing an estimation algorithm often begins by assuming a statistical mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 43 publications
3
98
0
Order By: Relevance
“…Definition 1 (Pseudo-true parameter [13]). Consider a signal sample y with probability density function f .…”
Section: Pseudo-true Parameters and Performance Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 1 (Pseudo-true parameter [13]). Consider a signal sample y with probability density function f .…”
Section: Pseudo-true Parameters and Performance Boundsmentioning
confidence: 99%
“…Here, it may be noted that the pseudo-true parameter θ 0 minimizes the Kullback-Leibler divergence between the distribution of the actual measurement, i.e., f , and the distribution of the model, encoded in the parametric likelihood L. Interestingly, it can be shown that the MLE corresponding to the misspecified model L converges to the pseudo-true parameter [13]. That is, as the number of samples from (1) tend to infinity, the maximumm likelihood estimator (MLE) derived under (4) tends to the pseudo-true parameter, making this an applicable definition of fundamental frequency for practical purposes.…”
Section: Pseudo-true Parameters and Performance Boundsmentioning
confidence: 99%
“…Definition 1 (Pseudo-true parameter [15]). Consider a signal sample with likelihood L, parametrized by the parameter vector ψ.…”
Section: Mismatched Estimationmentioning
confidence: 99%
“…where y is sampled from L, converges, under some regularity conditions, to the pseudo-true parameter θ 0 as the signal-to-noise ratio (SNR), or sample size, depending on the application, increases [15]. Herein, we are interested in estimating the parameters of purely sinusoidal and Lorentzian models when the actual measured signal may be Lorentzian or Voigt, respectively.…”
Section: Mismatched Estimationmentioning
confidence: 99%
See 1 more Smart Citation